The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/pere.12292
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional examination of marital conflict and subjective health over 16 years

Abstract: Guided by stress process perspectives, this study conceptualizes marital conflict as a multidimensional stressor to assess how three aspects of conflict—frequency of disagreements, breadth of disagreements, and cumulative disagreements—impact subjective health. Longitudinal data of married couples spanning 16 years (n = 373 couples) were analyzed using multilevel modeling. For husbands, more frequent disagreements than usual within a given year were associated with poorer subjective health. For wives, the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
(91 reference statements)
2
16
0
Order By: Relevance
“…These findings are consistent with other research highlighting the importance of having high quality relationships for other personal outcomes such as health and well-being. For example, although people in romantic partnerships categorically are physically healthier and live longer than their single counterparts (Holt-Lunstad et al, 2010;Johnson et al, 2000), these health advantages disappear when they are in high conflict partnerships (Shrout et al, 2019). The current findings suggest that identifying ways to improve satisfaction with existing relationships may therefore benefit both individuals and the broader social collective.…”
Section: Discussionmentioning
confidence: 73%
“…These findings are consistent with other research highlighting the importance of having high quality relationships for other personal outcomes such as health and well-being. For example, although people in romantic partnerships categorically are physically healthier and live longer than their single counterparts (Holt-Lunstad et al, 2010;Johnson et al, 2000), these health advantages disappear when they are in high conflict partnerships (Shrout et al, 2019). The current findings suggest that identifying ways to improve satisfaction with existing relationships may therefore benefit both individuals and the broader social collective.…”
Section: Discussionmentioning
confidence: 73%
“…Conflict has been associated with heightened depressive and anxiety symptoms, poorer subjective health, and increased functional impairment cross-sectionally and over time ( Wright and Loving, 2011 ; Loving and Slatcher, 2013 ). Using longitudinal data from a diverse sample of Black and White American couples over the first 16 years of marriage, my colleagues and I showed conflict impacted wives' and husbands' subjective health in different ways ( Shrout et al., 2019 ). Husbands had worse subjective health in the years the couples argued more often than usual, whereas disagreeing about several topics over 16 years predicted wives' poorer health.…”
Section: Health Consequence Of Stress In Couples: Actor Effectsmentioning
confidence: 99%
“…Because women tend to think about their relationships more than men do, they are generally more reactive to relational stress than men ( Kiecolt-Glaser and Newton, 2001 ). Recent research has shown more nuanced gender differences: more frequent conflict from year-to-year was related to husbands' poorer subjective health, whereas the pile up of conflict over 16 years was linked to wives' poorer subjective health ( Shrout et al., 2019 ).…”
Section: Actor and Partner Effects: A Comprehensive Dyadic Biobehavioral Stress Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study is to test an integrated conceptual model to explain the potential connection between relational turbulence and engagement in health‐compromising behavior. Much research has demonstrated the interconnections between intimate relationships and health (Loving & Slatcher, 2013; Shrout, Brown, Orbuch, & Weigel, 2019; Slatcher, 2010). In the present study, based on an integration of relational turbulence (Solomon et al, 2016; Solomon & Knobloch, 2004) and stress and coping theories (e.g., Lazarus & Folkman, 1984; McCubbin & McCubbin, 1996), we propose that a heightened sense of turbulence and turmoil in a relationship may drain partner's abilities to successfully cope with the ongoing stress, resulting in negative psychological and behavioral health outcomes, including stress, depression, and health‐compromising behavior.…”
Section: Introductionmentioning
confidence: 99%